马来西亚华小一二年级新旧华文课本与活动本词汇比较研究 - 邝, 美月 (2023)
Language textbooks are the primary medium for teaching and learning, while activity books are the key tool for consolidating what the students have learnt. Vocabulary learning in textbooks is the foundation of language learning. Therefore, the study of textbooks and activity books vocabulary has its significance and extremely important. The main purpose of this thesis is to examine, analyze and compare the old and new Chinese textbooks and activity books for Year1 and Year2, with the aim of understanding the appropriateness of the vocabulary level of these materials and whether the vocabulary features, quantity and exercise format of these materials are in line with the principles of writing textbooks for the lower grades, as well as analyzing the strengths and weaknesses of the old and new textbooks and activity books. The paper has used literature research method, comparative analysis and statistical research methods to conduct the study and analysis. The principle of textbook writing were also used as the basis for the research in this thesis. The results of the study revealed that there were no significant difference between the old and new versions of the Chinese textbooks for Year 1 and Year2 in the three major areas of vocabulary, word level and common words, and in the vocabulary exercise questions in their activity books, which means that the new version textbooks have not improved significantly. The vocabulary levels in both the old and new textbooks are within acceptable range. The number of words in each unit is not written on the principle of least to most in either edition. In term of vocabulary difficulty, the level 1 words in both the old and new versions are about 70% to 80%in Year 1; however, in Year 2, the level 1 words in both versions are only about 50%, which is not a reasonable arrangement. The word choice is consistent in both , with nouns, verbs and adjectives dominating. Finally, this thesis compares the first one hundred common words(in the place-order method) from the Yiwu Jiaoyu Changyongcibiao(Draft) with the old and new versions of the Year 1 and Year 2 textbooks. The analysis reveals that the difference in the proportion of the first one hundred words adopted from the Yiwu Jiaoyu Changyongcibiao(Draft)between the old and new version is not significant, Year 1 has more than 50% of both old and new textbooks, and Year 2 has more than 70% of both old and new textbooks. The old version conforming to the first one hundred words of Yiwu Jiaoyu Changyongcibiao (Draft) at a slightly higher rate than the new version. The number of vocabulary exercise questions in both new and old versions of the activity books for Year1 and Year2 is uneven for each unit and does not increase gradually, with a similar number of vocabulary exercise questions. The old activity book for Year 1 focuses more on writing skills. The vocabulary exercise questions form in both the old and new activity books was varied, and both vocabulary exercise questions were mainly fill-in-the-blanks questions and multiple-choice questions. All in all, there is no significant difference between the old and new versions of the textbooks and activity books. Finally, based on the finding of the study, this paper makes recommendations in order to give full play to the role of the Malaysian Chinese textbooks in enabling students to master the Chinese language more effectively, and hope that through this paper, it will promote the research o Chinese textbooks.